Constraint performance pressure tracking control with asymmetric continuous friction compensation for booster based brake-by-wire system. (15th July 2022) - Ji, Yuan; Zhang, Junzhi; He, Chengkun; Ma, Ruihai; Hou, Xiaohui; Hu, Hanyang
Highlights: Pressure control significant for precise braking of electro-hydraulic braking system. High accuracy main cylinder pressure tracking method for motor-booster EHB system. Asymmetric continuous friction model facilitates tracking controller design. Constraint tracking performance with a predefined error function realized. Disturbance updated based on measured pressure and estimated parameter. Abstract: Pressure control of the electro-hydraulic brake-by-wire system (EHB) is of great significance in achieving precise braking maneuvers for the brake-by-wire vehicle. In this study, a high accuracy main cylinder pressure tracking method with exact performance boundary is proposed for the mainstream motor-booster EHB system. By considering the clearance in the mechanical transmissions, a more applicable continuous friction model is derived based on experimental identification and used as direct feedforward input to facilitate the pressure tracking controller design. A constraint adaptive robust controller is proposed by combining adaptive robust control and prescribed performance mechanism to realize constraint pressure tracking. The unknown key parameter is estimated through a new adaptive law driven by both tracking error and observation error. System disturbance is observed by an extended state observer using the estimated parameter. The stability of the closed-loop system is proved based on the Lyapunov theory. Hard-ware-in-loop tests with various typical pressure tracking scenarios were performed to verify the superiority in pressure tracking with no violation of the predefined error boundary.